The Influence of Workplace Spirituality and Organizational Culture on Job Performance among Employees in Private Companies in Nonthaburi Province - Chaiprasert, Natthaphorn (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study pursued two primary objectives: (1) to examine the levels of workplace spirituality, organizational culture, and job performance among employees of private companies in Nonthaburi Province; and (2) to analyze the influence of workplace spirituality and organizational culture on job performance among employees of private companies in Nonthaburi Province. A quantitative research methodology was employed. The sample consisted of 384 employees from private companies in Nonthaburi Province, selected through proportionate stratified random sampling across six districts, with accidental sampling applied at the company level. Data were collected via a structured questionnaire and analyzed using descriptive statistics—including means and standard deviations—as well as multiple regression analysis. The findings revealed that all three variables were rated at a high level overall. Organizational culture yielded the highest mean score, followed by workplace spirituality and job performance, respectively. Both variables exerted a statistically significant positive influence on job performance (p < .001), jointly accounting for 76.8% of the variance in job performance (R² = .768). Workplace spirituality demonstrated a stronger effect than organizational culture (β = .534 and β = .388, respectively). The findings indicate that employee job performance is shaped by the integration of individual-level internal factors and organizational contextual factors, with workplace spirituality possessing significantly greater predictive power.